2007
DOI: 10.1586/14789450.4.3.363
|View full text |Cite
|
Sign up to set email alerts
|

Plasma/serum proteomics: pre-analytical issues

Abstract: High-throughput proteomics technologies tend to provide highly sensitive information about living tissues and biological fluids. Analytes are characterized by intrinsic and extrinsic properties, the latter depending on each phase of their preparation, sometimes adding artifacts with crucial repercussions in result reliability and interpretation. This review aims to address some issues that can be encountered when handling plasma and serum in experimental and clinical proteomic settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 70 publications
0
40
0
Order By: Relevance
“…Therefore, the differences between plasma and serum are the clot and the chemical used as anticoagulant. However, using proteomic tools, the differences are more complex; thousands of protein fragments are generated through the coagulation cascade, mainly through proteolysis induced by thrombin and many other serine proteases that are activated during coagulation [3]. The fasting condition of the individual -whether they take drugs or are a smoker, and their gender, age, weight, and size, or physical activities -may directly influence the blood content and measured parameters.…”
Section: Pre-and Analytical Issues and Proteomicsmentioning
confidence: 99%
“…Therefore, the differences between plasma and serum are the clot and the chemical used as anticoagulant. However, using proteomic tools, the differences are more complex; thousands of protein fragments are generated through the coagulation cascade, mainly through proteolysis induced by thrombin and many other serine proteases that are activated during coagulation [3]. The fasting condition of the individual -whether they take drugs or are a smoker, and their gender, age, weight, and size, or physical activities -may directly influence the blood content and measured parameters.…”
Section: Pre-and Analytical Issues and Proteomicsmentioning
confidence: 99%
“…However, it is not well understood how protein expression in tissues reflect measurable levels in the serum or plasma that would allow the monitoring of the pathophysiological status of respective tissue (Anderson, 2010;Barelli, Crettaz, Thadikkaran, Rubin, & Tissot, 2007;Farrah et al, 2011;Hanash et al, 2008;Issaq, Xiao, & Veenstra, 2007). This may partially stem from the trend that the comprehensive analysis of tissue relevant proteins in less invasive clinical matrices such as the plasma or serum has been a daunting task for MS based methods despite all their latest technological advancements (Anderson, 2010;Farrah et al, 2011;Hanash et al, 2008).…”
Section: The Quantitative Proteomic Profiling Of Clinical Serum Samplmentioning
confidence: 99%
“…Another factor is associated with the large biological heterogeneity of the specimens tested. Unless the clinical samples have well defined inclusion and inclusion criteria along with effective sample procurement and handling protocols at statistically significant numbers to address a hypothesis at hand (i.e., power analysis), the analytical output will lack accuracy and precision to be of any value to the clinician (Adewale et al, 2008;Anderson, 2010;Barelli et al, 2007;Farrah et al, 2011). Another impediment is the lack of lower-cost and high-throughput validation protocols to compensate for the large number of samples that need to be analyzed.…”
Section: Immuno-srm (Siscapa)mentioning
confidence: 99%
“…High abundance proteins account for about 90% of the whole weight. 27 In this work, about 20 mg crude plasma was loaded on the SCX column at pH 2.0. We chose 5 pH steps as the first dimension and 20 salt steps in total across the whole pH range as the second dimension.…”
Section: Speculations Upon Chromatographic Behavior Of Standardmentioning
confidence: 99%
“…Comparison of SCX and other fractionation methods as the first dimension revealed that SCX can identify more proteins than gel slices and liquid phase isoelectric focusing (IEF). 26 Plasma is known to be a classical proteomic sample with "haystack" of proteins 27 distributed in a dynamic concentration range of more than 10 orders. [28][29][30][31][32][33] Although investigation of plasma holds the promise of a resolution in disease diagnosis and therapeutic monitoring, 34 most potential biomarkers are present in quite low abundance.…”
Section: Introductionmentioning
confidence: 99%